The Reformulation of Abortion Regulations: Study of the Ratio Legis and Ius Constituendum: Reformulasi Peraturan Aborsi: Studi tentang Rasio Legis dan Ius Constituendum - Putri, Dinda Fefty Miranda; Azizah, Ainul; Tannuwijaya, Fanny (Rechtsidee, 2022)
Abortion can actually be carried out with various special provisions based on Law no. 36 of 2009 concerning Health (Health Law) and Government Regulation no. 61 of 2014 concerning Reproductive Health (PP Kespro). This study aims to find out the legal review regarding abortion in relation to the principle of protection for rape victims, as well as to study and formulate an appropriate and appropriate timeframe for carrying out an abortion based on the principle of protection for rape victims. This research is normative legal research by prioritizing conceptual and statutory approaches. The results of the study confirm that the legal ratio for setting the fetal age limit related to abortion for rape victims does not actually explain the reasons or the urgency why the 6 weeks and 40 (forty) days are calculated from the first day of the last menstrual period formulated by the formulators of laws and regulations and only refers to The principle of protecting victims is currently the main orientation of Indonesian criminal law. In the future, the regulation on the principle of protection for victims related to the fetal age limit related to abortion for victims of rape, namely: it is necessary to emphasize the principle of protection for victims in the Health Law. The recommendation of this research is the need for a revision of the Health Law and PP on Produce as based on WHO provisions and with relevant medical considerations.